Breaking Into New Markets - Newfarmer, Richard (World Bank, 2012)
This book takes a fresh look at export diversification. It concludes that much of the recent literature, though novel, has focused excessively on simply adding new products to export portfolios. One branch of these studies centers on the 'discovery' of exports, and it argues that the threat of entry (imitation) leads to an underinvestment in bringing new products to the global market. Another analytical branch focuses on changing the contents of an export portfolio to mirror the exports of countries with higher incomes on the grounds that these lead to higher productivity. Both strands implicitly point to the need for careful yet active government policies. While such policies are important, this book argues for a more comprehensive view of diversification and hence a more comprehensive trade policy strategy-one that takes into account improving the quality of existing exports, breaking into new geographic markets, and increasing services exports. This publication has been tailored to policy makers, their staffs, and the international development community at large. It is a collection of short articles that summarize major issues and policies on particular topics. Many of the chapters are digests of more formal studies but are presented here with a minimum of underlying econometric and theoretical detail of less interest to policy makers. As the World Bank increases its efforts on 'aid for trade,' Staff are working with countries to help diversify their exports. Along with other development partners, the Bank is providing enhanced assistance to improve competitiveness, facilitate trade, improve trade-related services, and exploit regional and multilateral initiatives to open markets for developing countries. This book makes a substantial contribution to the efforts of developing countries to use the global economy to spur growth and reduce poverty.